PENGARUH LEMBAR KERJA SISWA (LKS) TERINTEGRASI SISTEM GERAK TUBUH MANUSIA PADA MATERI GERAK MELINGKAR, DINAMIKA DAN HUKUM NEWTON TERHADAP HASIL BELAJAR FISIKA DALAM PEMBELAJARAN COOPERATIVE PROBLEM SOLVING DI KELAS X SMA N 5 PADANG - Riri Yandari; Syakbaniah Syakbaniah; Ratnawulan Ratnawulan (Universitas Negeri Padang, 2016)
One of the factors causing low learning outcomes Physics is the lack of ability of the students in solving problems. Businesses that can be done to improve students' ability to solve problems is to use a worksheet integrated motion system of the human body with Cooperative Problem Solving learning model. This study aims to investigate the influence and contribution of Student Worksheet integrated motion system of the human body in Cooperative Problem Solving learning on Physics learning outcomes in Class X SMAN 5 Padang. This type of research is a quasi experimental research with the study design randomized control group only design. The study population were students of class X SMAN 5 Padang enrolled in the academic year 2015/2016. Sampling was done by purposive sampling techniques, the class obtained as an experimental class X 10 and X 11 as the control class. Data on research are physics students' learning outcomes data, value data Student Worksheet integrated motion system of the human body. The research instrument was a written test for cognitive, observation sheet for affective, and psychomotor rubric for scoring. Data analysis used the equality of two average on the real level of 0.05, regression and correlation tests for cognitive, affective, and psychomotor. The results showed that the average value of Physics graders experimental and control group was 81.33 and 74.57 for the cognitive, 83.08 and 78.65 for affective domain, and 81.33 and 76.96 for psychomotor. Based on the equality test two averages in the cognitive, affective and psychomotor using t test, the result tcount> ttabel. Results of regression and correlation test obtained contributions Student Worksheet integrated motion system of the human body on the cognitive amounted to 90.27%, the affective domain by 60.56%, and the psychomotor amounted to 82.82%. Conclusion of the study is 1) there is a significant influence Student Worksheet integrated motion system of the human body in a circular motion materials, dynamics and Newton's laws against Physics learning outcomes in Cooperative Problem Solving learning in Class X SMAN 5 Padang on the real level of 0.05 is acceptable, 2) there is a meaningful contribution Student Worksheet integrated motion system of the human body in a circular motion materials, dynamics and Newton's laws against Physics learning outcomes in Cooperative Problem Solving learning in class X SMAN 5 Padang